Evaluasi Kualitas Antarmuka Pengguna Katalog Digital Mobil Bekas Zae Motor Menggunakan Metode Heuristic Evaluation - Andrean Mulyadi Aming (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The web-based used car trading information system developed for CV. Zae Motor was built to replace conventional business processes such as manual stock recording, customer data management, and sales documentation. However, the availability of functional features does not automatically guarantee a good user experience, since a system that is difficult to operate can trigger input errors and reduce user satisfaction. This study aims to evaluate the quality of the user interface of the Zae Motor digital car catalog through Heuristic Evaluation based on Jakob Nielsen's ten usability principles. The evaluation focused on three main modules, namely the guest catalog and vehicle detail pages, the car-selling submission form, and the admin dashboard used for inventory and transaction management. Three expert evaluators with a background in information systems and user interface design independently examined each module against the ten heuristic principles and assigned a severity rating on a 0–4 scale for every violation found. The results indicate that the interface generally meets usability standards, with strong performance in Consistency and Standards, Error Prevention, and Match between System and the Real World, mainly due to the use of the Bootstrap framework and everyday automotive terminology. The main area requiring improvement is Flexibility and Efficiency of Use, particularly the absence of an advanced search filter. These findings provide practical recommendations to strengthen the usability of the Zae Motor system before it is deployed for full public use.